Rapid Detection and Quantification of Gambir Adulteration Using ATR-FTIR Spectroscopy Coupled with Chemometric Analysis - Satria, Dedi; Eranisa, Yenni; Arel, Afdhil (Jurnal Riset Kimia, 2025)
Gambir (an extract from Uncaria gambir Roxb.) is a valuable Indonesian herbal product susceptible to adulteration for economic gain. In this study, we developed a rapid, non-destructive method to detect and quantify adulteration in gambir using Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR) spectroscopy combined with chemometric analysis. In total, 32 gambir samples were prepared, including authentic gambir, samples adulterated with a fertilizer (SP36) at 0–50% w/w, quality control (pooled) samples, and a market sample of unknown purity. FTIR spectra (4000–600 cm−1) were collected. The spectral data were preprocessed and analyzed with PCA, SIMCA, and PLS-R. PCA revealed clear clustering of samples according to adulterant concentration, with the first two principal components capturing more than 99% of total variance. Chemometric classification models successfully distinguished authentic gambir from adulterated samples: SIMCA showed clear separation, with the 1% adulterant concentration sample clustering near authentic gambir, while the PLS-R calibration model achieved excellent linearity (R² ≈ 0.988) in predicting adulterant levels, with low RMSECV (≈ 0.0375) and a detection limit of ~0.54% adulterant concentration. When applied to a gambir sample obtained from the market, the PLS-R model indicated ~25% adulterant concentration. These results demonstrate that FTIR spectroscopy combined with multivariate analysis can effectively detect and quantify even low levels of adulterant concentration in gambir. This approach offers a fast and reliable tool for quality control and authentication of herbal products prone to adulteration.